Psychophysiological Stress Assessment Using Biofeedback - Khazan, Inna (MyJove Corporation, 2009)
In the last half century, research in biofeedback has shown the extent to which the human mind can influence the functioning of the autonomic nervous system, previously thought to be outside of conscious control. By letting people observe signals from their own bodies, biofeedback enables them to develop greater awareness of their physiological and psychological reactions, such as stress, and to learn to modify these reactions. Biofeedback practitioners can facilitate this process by assessing people s reactions to mildly stressful events and formulating a biofeedback-based treatment plan. During stress assessment the practitioner first records a baseline for physiological readings, and then presents the client with several mild stressors, such as a cognitive, physical and emotional stressor. Variety of stressors is presented in order to determine a person's stimulus-response specificity, or differences in each person's reaction to qualitatively different stimuli. This video will demonstrate the process of psychophysiological stress assessment using biofeedback and present general guidelines for treatment planning.